Metaphor and Interpretation of Social Criticism of Community in Iwan Fals Albums - Oktavia, Wahyu (Jurnal KATA, 2019)
This research aims to describe the metaphor and interpretation of social criticism in Iwan Fals song albums. The use of qualitative descriptive method leads the result of the research to elaborate the data by words rather than numbers. The data of the research was taken from the lyrics of Iwan Fals’ songs; “Opiniku”, “Sumbang”, “Tikus-Tikus Kantor”, “Besar Kecil”, “Dunia Binatang”, “17 Juli 1996”, “Buktikan”, dan “Kuda Lumping”. Then, the researcher observed and marked the lyrics as the technique in collecting the data. By the results, it can be concluded four metaphorical classifications; animal metaphor, anthropomorphic, from concrete to abstract, and sinaesthetics, the results of the study show that Iwan Fals uses many metaphors of animals such as tigers, snakes, elephants, rats, cats, shrimp, dogs, crocodiles, dinosaurs, lizards, lizards, ducks, parrots and lizards.